Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study. Issue 12 (2nd December 2018) - Zhang, Ting; Pan, Da; Su, Ming; Fu, Ling-Meng; Miao, Cai-Yun; Yan, Qing-Yang; Wang, Jing; Yang, Li-Gang; Wang, Shao-Kang; Sun, Gui-Ju
ABSTRACT: The goal of this study was to find the relationship between dietary nitrite and risk of esophageal cancer, and determine the amount of nitrite intake to establish the oral highest daily intake to prevent the occurrence of esophageal cancer. Duplicate portions of three-consecutive-day diets were collected from 100 patients with esophageal precancerous lesions and 100 controls. The average nitrite daily intakes for esophageal precancerous lesions and normal people were 15.72 mg/d and 11.11 mg/d. The median nitrite daily intakes for cases and controls were 8.76 mg/d and 5.33 mg/d. Positive association was observed between the risk of esophageal precancerous lesions and dietary nitrite intake ( p = 0.035). An increased risk of esophageal precancerous lesions was observed for cases or controls in the highest intake quartile of nitrite (highest vs. lowest quartile odds ratio ( OR ) = 2.256, 95% confidence interval ( CI ): 1.012–5.026). These results suggest that dietary nitrite intake may influence the risk of esophageal cancer; populations with high incidence of esophageal cancer should take control of nitrite intake as one of the measures to prevent esophageal cancer.